Sulfur isotopes of sulfate measurements from a Greenland ice core (1850-2006) ... - Jongebloed, Ursula; Alexander, Becky; Cole-Dai, Jihong; Schauer, Andrew; Larrick, Carleigh; Hattori, Shohei; Salimi, Sara; Edouard, Shana; Geng, Lei (NSF Arctic Data Center, 2023)
Anthropogenic sulfate aerosols are estimated to have offset sixty percent of greenhouse-gas-induced warming in the Arctic, a region warming four times faster than the rest of the world. However, sulfate radiative forcing estimates remain uncertain because the relative contributions from anthropogenic versus natural sources to total sulfate aerosols are unknown. Here we measure sulfur isotopes of sulfate in a Summit, Greenland ice core from 1850 to 2006 CE to quantify the contribution of anthropogenic sulfur emissions to ice core sulfate. We use a Keeling Plot to determine the anthropogenic sulfur isotopic signature (δ34Santhro = +2.9  0.3 ‰), and compare this result to a compilation of sulfur isotope measurements of oil and coal. Using δ34Santhro, we quantify anthropogenic sulfate concentration separated from natural sulfate. Anthropogenic sulfate concentration increases to 68 ± 7% of non-sea-salt sulfate (65.1 ± 20.2 µg kg-1) during peak anthropogenic emissions from 1960 to 1990 and decreases to 45 ± 11% ...